Legend of Pashas. Polyphonic speech - Cuba, María del Carmen (2022)
In the legend or discursive text, the narrator becomes an enunciator, whose language results in the enunciation that is the story. The legend of Pashas, originally from the Cabana district, tells the story of a marriage alliance between a young man living in Mashgonga hill, the upper part of this town, with a young woman who lived in Llactabamba hill, the lower zone or valley; whose parents (both curacas) were enemies. This marriage, by choosing Pashas hill as their residence, an intermediate place between Mashgonga and Llactabamba, ends the enmity of their parents and gives rise to a new population. In the discursive text of this legend through multiple voices (discursive polyphony), the narrator qualifies languages, dialects, historical and cultural events that he has heard in Cabana, also reflected in place names.